2020
DOI: 10.1002/jcla.23320
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelet infiltration as independent prognostic marker for gastric adenocarcinomas

Abstract: Background In recent years, the relationship between malignant tumors and platelets has been paid more attention. The increase of platelets is an independent risk factor for the poor prognosis of some malignant tumors. Methods This study retrospectively analyzed the clinical and pathological data of 114 patients with initial gastric cancer from August 2005 to August 2018 in Shandong Provincial Hospital. Single‐factor and multifactor survival analysis were used to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Previously, several investigations have found that platelet count is an independent factor affecting the survival rate of patients with refractory ascites. 26 Therefore, PLT count is related to postoperative liver function and survival rate, and a higher PLT count is beneficial to liver function. 27 In the present study, miR-9a-5p had the highest AUC value in patients with relapse.…”
Section: A B Cmentioning
confidence: 99%
“…Previously, several investigations have found that platelet count is an independent factor affecting the survival rate of patients with refractory ascites. 26 Therefore, PLT count is related to postoperative liver function and survival rate, and a higher PLT count is beneficial to liver function. 27 In the present study, miR-9a-5p had the highest AUC value in patients with relapse.…”
Section: A B Cmentioning
confidence: 99%
“…[9][10][11] On the other hand, various tumors have been reported to be closely related to systemic immune status and coagulation, including fibrinogen (FIB), albumin, pre-albumin, platelets, etc. [12][13][14] It has been shown that reduced levels of albumin and prealbumin in the body will lead to a reduced nutritional status and impaired immune function in patients, thus promoting tumour progression. 15,16 FIB increases during tumour development, promoting platelet adhesion and binding to growth factors, accelerating tumour cell adsorption and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that platelet (PLT) regulates tumorigenesis and tumor progression, such as GC, prostate cancer, lung cancer, breast cancer, and colorectal cancer etc ( Oh et al, 2019 ; Garmi et al, 2020 ; Meikle et al, 2020 ; Plantureux et al, 2020 ; Rudzinski et al, 2020 ; Singla et al, 2020 ; Wang et al, 2020 ). For examples, PLT directly promote epithelial-mesenchymal transformation (EMT) of malignant tumors by producing TGF-β, leading to poor prognosis ( Labelle et al, 2011 ; Heldin et al, 2012 ; Guo et al, 2019 ; Chong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%